2008
DOI: 10.3810/pgm.2008.11.1929
|View full text |Cite
|
Sign up to set email alerts
|

New Quadrivalent HPV Vaccine Developments

Abstract: Human papillomavirus infection is the most prevalent sexually transmitted disease in the world and is responsible for cervical, vulvar, and vaginal cancers, as well as genital warts. A vaccine against HPV types 6, 11, 16, and 18 has been available since 2006 and has been approved for the prevention of cervical cancer, cervical precancers, and genital warts. Recently, the vaccine also received approval for the prevention of vulvar and vaginal cancers in women aged 9 to 26 years. Although Guillain-Barré syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…1,5 Two prophylactic HPV vaccines, Cervarix ® (HPV- The HPV-6/11/16/18 vaccine contains L1 VLPs for HPV types 6 and 11, which cause genital warts, and 16 and 18, and is formulated with a proprietary amorphous aluminum hydroxyphosphate sulfate (AAHS) adjuvant. 8,9 In the short to medium term, clinical studies have shown both vaccines to be highly efficacious against persistent HPV-16/18 infection and their associated precancerous lesions. [10][11][12][13] Protection has been demonstrated for up to 6.4 y post-vaccination for the HPV-16/18 vaccine 10,13-15 and up to 5 y post-vaccination for the licensed formulation of the HPV-6/11/16/18 vaccine, 12,[16][17][18] although there has been a longer follow-up with a prototype HPV-16 monovalent vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Two prophylactic HPV vaccines, Cervarix ® (HPV- The HPV-6/11/16/18 vaccine contains L1 VLPs for HPV types 6 and 11, which cause genital warts, and 16 and 18, and is formulated with a proprietary amorphous aluminum hydroxyphosphate sulfate (AAHS) adjuvant. 8,9 In the short to medium term, clinical studies have shown both vaccines to be highly efficacious against persistent HPV-16/18 infection and their associated precancerous lesions. [10][11][12][13] Protection has been demonstrated for up to 6.4 y post-vaccination for the HPV-16/18 vaccine 10,13-15 and up to 5 y post-vaccination for the licensed formulation of the HPV-6/11/16/18 vaccine, 12,[16][17][18] although there has been a longer follow-up with a prototype HPV-16 monovalent vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…69 El costo actual de las vacunas hace inviable su promoción poblacional en países pobres y de ingresos medios. A la fecha la mayoría de los países desarrollados han iniciado programas de vacunación universal en niñas adolescentes, pero muy pocos países de América Latina los han iniciado.…”
Section: Vacunas Contra La Infección Por Vph Una Perspectiva De Saluunclassified
“…Since Edward Jenner's pioneered the concept of vaccination with a smallpox vaccine in 1796, the suppression and control of a wide range of epidemic and pandemic infectious diseases has effectively been accomplished with vaccines (Bernstein, 2007;Heaton and Ciarlet, 2007;Matson, 2006;O'Ryan, 2007;Tovar and Bazaldua, 2008;Zimmerman, 2007). However, vaccines are not yet available for important deadly diseases such as malaria, AIDS and hepatitis C, and there is a clear need for a more efficacious vaccine against tuberculosis, a major cause of illness and death despite the widespread use of Bacillus Clamette-Guérin (BCG) vaccine.…”
Section: The Importance Of Innovative Vac-cine Production Technologiesmentioning
confidence: 99%
“…However, vaccines are not yet available for important deadly diseases such as malaria, AIDS and hepatitis C, and there is a clear need for a more efficacious vaccine against tuberculosis, a major cause of illness and death despite the widespread use of Bacillus Clamette-Guérin (BCG) vaccine. In addition, every year an estimated 2.5 million people worldwide die from vaccine-preventable diseases (VPDs), reflecting the underuse of available vaccines (Tovar and Bazaldua, 2008). Most deaths induced by VPDs occur in developing areas, which have low vaccine coverage rates due to low income, lack of medical infrastructure, lack of cold chain facilities, etc.…”
Section: The Importance Of Innovative Vac-cine Production Technologiesmentioning
confidence: 99%
See 1 more Smart Citation